The Significant Process Variable of Tea Powder Production Based On Spray Dry Method - Muhammad Arifuddin Fitriady; Alfissyahriyah Nur Rohmah; NINO RINALDI; Agustian; ANNY SULASWATTY; Shabri Shabri (Jurnal Sains Materi Indonesia, 2024)
Polyphenol, which is very beneficial to the human body, especially as an obesity inhibitor, is one of the leading nutrient content in green tea leaves. To increase popularity as well as practicability, product development needs to be conducted, one of which is to produce an effervescent instant tea. However, a high-density instant tea powder is required in this product development. This study was conducted to predict the significant process variables which affect the density as well as the yield of the instant tea powder. The exploration of significant process variables was conducted based on the Design of the Experiment, while the tea extract was produced using maceration techniques. Maltodextrin was added to the tea extract based on the concentration filler variable. The instant tea powder was produced by the spray drying method, which variable includes the concentration of maltodextrin (filler), the pump flow rate (feed pump), the outlet temperature (Tout), the fan speed, and the atomization air pressure (nozzle). The tapped density of the instant tea powder was analysed and the yield was calculated for each condition. Based on the Pareto graph, it was found that the atomization air pressure (nozzle) is the most significant variable in the spray dry process of instant tea powder.